2018
DOI: 10.3389/fphys.2018.01092
|View full text |Cite
|
Sign up to set email alerts
|

TRIP-1 Promotes the Assembly of an ECM That Contains Extracellular Vesicles and Factors That Modulate Angiogenesis

Abstract: Transforming growth factor beta receptor II interacting protein-1 (TRIP-1) was recently localized in the mineralized matrices of bone and dentin. The function of TRIP-1 in the ECM is enigmatic, as it is known to function as an intracellular endoplasmic reticulum protein during protein synthesis. Based on its localization pattern in bones and teeth, we posited that TRIP-1 must function as a regulatory protein with multiple functions during mineralization. In this study, we determined the in vivo function of TRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…PRS is a non-specific stain for a variety of collagen types that reveals information about a tissue's collagen content, molecular order, and organization (Lattouf et al, 2014). Our group has previously used the PRS method in conjunction with polarized light microscopy to quantify the de novo collagen synthesis in a subcutaneous implantation model (Chen and George, 2018). In this study, polarized light microscopy revealed significant differences in the absolute angles of collagen fibers between the genotypes.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…PRS is a non-specific stain for a variety of collagen types that reveals information about a tissue's collagen content, molecular order, and organization (Lattouf et al, 2014). Our group has previously used the PRS method in conjunction with polarized light microscopy to quantify the de novo collagen synthesis in a subcutaneous implantation model (Chen and George, 2018). In this study, polarized light microscopy revealed significant differences in the absolute angles of collagen fibers between the genotypes.…”
Section: Discussionmentioning
confidence: 80%
“…Polarized images of the Sirius Red stained sections were analyzed using the opensource CT-FIRE software (Bredfeldt et al, 2014). Regions of interest (dentin, PDL, and bone) were annotated using the ROI manager tool and quantitative CT-FIRE analysis was performed on each to obtain collagen fiber length, width, and angle, as previously published (Chen and George, 2018). For WT versus Hyp comparisons in Figure 1, statistical analysis was performed using multiple t-tests with the Holm-Sidak correction for multiple comparisons, alpha = 0.05.…”
Section: Picrosirius Red Staining and Ct-fire Analysismentioning
confidence: 99%
“…Matrix vesicles are observed as aggregates in some areas or scattered among collagen fibrils in others, consistent with previous studies that show aggregates of matrix vesicles on mineralizing osteoblasts. [45][46][47] This further suggests that the cells are engaged in the primary phase of mineralization.…”
Section: Monoculture: Morphological Characterizationmentioning
confidence: 97%
“…Immunogold labeling also suggested that TRIP1 could bind to monomeric collagen aggregates. These observations suggest that TRIP1 in the ECM could bind both collagen and calcium ions to initiate matrix mineralization (Chen and George 2018).…”
Section: Matrix Proteins In Dentinmentioning
confidence: 99%